2014
DOI: 10.3896/ibra.1.53.1.04
|View full text |Cite
|
Sign up to set email alerts
|

A survey on some factors potentially affecting losses of managed honey bee colonies in Luxembourg over the winters 2010/2011 and 2011/2012

Abstract: Publication details, including instructions for authors and subscription information: http://www.tandfonline.com/loi/tjar20 A survey on some factors potentially affecting losses of managed honey bee colonies in Luxembourg over the winters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…1, Clermont et al, 2014). Even though the highest virus levels within the present study for ABPV, BQCV, DWV, and VdMLV were observed at the northern Heinerscheid location, where all colonies were lost in both years surveyed, no significant differences towards other locations could be demonstrated as far as these viruses were concerned.…”
Section: Regional Aspectscontrasting
confidence: 66%
See 1 more Smart Citation
“…1, Clermont et al, 2014). Even though the highest virus levels within the present study for ABPV, BQCV, DWV, and VdMLV were observed at the northern Heinerscheid location, where all colonies were lost in both years surveyed, no significant differences towards other locations could be demonstrated as far as these viruses were concerned.…”
Section: Regional Aspectscontrasting
confidence: 66%
“…De Smet et al (2012) found that multiple infections with ABPV, BQCV, CBPV, DWV, SBV, and SBPV, in Northern Belgium, could be predicted from the prevalence of individual viruses, suggesting independent occurrence of the viruses. A previous survey indicated that 16.8% of the managed honey bee colonies in Luxembourg were lost over the winter of 2010/2011, and 21.8% over the winter of 2011/2012 (Clermont et al, 2014). In contrast to other surveys, a clear spatial pattern of losses was observed.…”
Section: Bee Viruses In Luxembourgmentioning
confidence: 71%
“…High honey bee colony losses have been observed in recent years in many countries (Neumann and Carreck, 2010;Potts et al, 2010), notably from 2006 onwards in the USA (Ellis et al, 2010;vanEngelsdorp et al, 2007vanEngelsdorp et al, , 2008vanEngelsdorp et al, , 2010vanEngelsdorp et al, , 2011vanEngelsdorp et al, , 2012Spleen et al, 2013;Steinhauer et al, 2014) but subsequently in many other places (Aston, 2010;Charriere and Neumann, 2010;Currie et al, 2010;Gray et al, 2010;Hatjina et al, 2010;Ivanova and Petrov, 2010;Mutinelli et al, 2010;Tlak Gajger et al, 2010;Topolska et al, 2010;Vejsnaes et al, 2010;van der Zee, 2010;van der Zee et al, 2012;Clermont et al, 2014;Pirk et al, 2014). This has led to intensive co-operation between honey bee experts to investigate this problem from different perspectives, including epidemiology and experimental approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Documenting colony losses is critical for putting losses into context and identifying potential causes of mortality, especially in different regions. To better understand the distribution of colony losses, researchers have conducted surveys at national or regional scales (Aston 2010;Brodschneider et al 2010;Charrière and Neumann 2010;Clermont et al 2014;Dahle 2010;Gajger et al 2010;Gray et al 2010;Hatjina et al 2010;Ivanova and Petrov 2010;Mutinelli et al 2010;Neumann and Carreck 2010;Nguyyen et al 2010;Pirk et al 2014;Potts et al 2010b, Soroker et al 2010Topolska et al 2010;van der Zee 2010;van der Zee et al 2012;van der Zee et al 2013;van der Zee et al 2014;Vejsnaes et al 2 0 1 0 ) , i n c l u d i n g t h e U n i t e d S t a t e s (vanEngelsdorp et al 2007(vanEngelsdorp et al , 2008(vanEngelsdorp et al , 2012Spleen et al 2013;Steinhauer et al 2014). Multi-year records are especially important to understanding the variability of losses.…”
Section: Introductionmentioning
confidence: 99%